Surgical Diseases of the Pancreas and Biliary Tree (Springer Singapore, 2018)
This book provides an evidence-based approach to the diagnosis and surgical management of the diseases of the pancreas and biliary tree, highlighting the most recent findings. The chapters are designed to accompany the reader on a step-by-step approach to the patient, providing the latest evidence to justify each recommendation. Wherever feasible and indicated, emphasis is placed on the use of tables and algorithms to simplify decision-making. The information contained in this well-referenced book is thus relevant not only to practicing pancreatobiliary and general surgeons, but also offers valuable guidance for surgical trainees. This book covers 14 diseases of the pancreas and biliary tree, from the more common gallstones and common bile duct stones, acute and chronic pancreatitis, to more complex benign conditions such as biliary fistulae and strictures, as well as cystic tumors of the pancreas, and finally the major malignancies include gallbladder cancer, pancreatic cancer and hilar cholangiocarcinoma. .